2017
DOI: 10.24262/jmd.2.2.17003
|View full text |Cite
|
Sign up to set email alerts
|

Dig the root of cancer: targeting cancer stem cells therapy

Abstract: Cancer stem cells are a subpopulation of cancer cells which have stem cell characteristics and play vital role in tumor formation, metastasis, relapse and resistance to chemo-drugs. Exploring drugs or designing novel approaches to target cancer stem cells will contribute greatly to cancer therapy. The first step of exploring effective drugs to cancer stem cells is to acquire cancer stem cells and characterize their properties. Developing the targeting drugs could be based on the characteristics of cancer stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The characteristics of cancer stem cells include multidirectional differentiation potential, self-renewal ability, multiple drug resistance, and the ability to influence tumor development (5). Therefore, there is increasing evidence that cancer stem cells in tumor tissues may contribute to recurrence in many cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of cancer stem cells include multidirectional differentiation potential, self-renewal ability, multiple drug resistance, and the ability to influence tumor development (5). Therefore, there is increasing evidence that cancer stem cells in tumor tissues may contribute to recurrence in many cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The primary causes of mortality in PTC patients include local recurrence and distant metastases. Recent evidence indicates that these events occur due to the presence of a specific population of cancer stem cells (CSCs), which exist within various tumor types (3); these are considered the root cause of tumorigenesis, metastasis and recurrence (4,5). Recently, studies utilizing cancer stem cell markers, CD133, CD44, EpCAM, LGR5 and ALDH1, have confirmed the presence of CSCs in lung, breast, pancreatic and prostate cancers (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is a severe disease leading to millions of death worldwide 1 . Oral cavity cancer is a malignant tumor with high incidence, which is known for its poor prognosis and high mortality rates because of features such as high invasiveness and metastasis 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The patient-derived iPSC can be used to repair or regenerate the tissues which were damaged due to treatment 106,107 . Cancer stem cells (CSCs) are known to attract normal stem cells which is the reason why normal stem cells are being engineered to target CSCs to ensure the high therapeutic efficacy of cancer therapy and also prevent the recurrence of the tumor 108 .…”
Section: From Basic Biology To Clinical Applicationmentioning
confidence: 99%